2018
DOI: 10.1177/0954410018782511
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bypass ratio on subsonic and correctly expanded sonic co-flowing jets with finite lip thickness

Abstract: The effects of bypass ratio on co-flowing subsonic and correctly expanded sonic jet decay have been studied experimentally. Co-flowing jets with lip thickness 1.0Dp (where Dp is the diameter of primary nozzle and is equal to 10 mm) with bypass ratios of around 0.7, 1.4, and 6.4 at primary jet exit Mach numbers 0.6, 0.8, and 1.0 have been analyzed. A single free jet equivalent to primary nozzle of the co-flowing nozzle was considered for comparison. Primary jet centerline total pressure decay, spread, and stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…The numerical study was done for the following LTs: 1.0 D p , 1.5 D p , 2.0 D p , 2.5 D p , 3.0 D p , 3.5 D p , 4.0 D p , 4.5 D p , 5.0 D p , 6.0 D p , 7.0 D p , 8.0 D p , 10.0 D p and 15.0 D p . The results for LT 1.0 D p and 1.5 D p obtained from the experimental study correlates well with CFD results (Naren Shankar et al, 2016;Naren Shankar, 2017;Naren Shankar et al, 2018;Thanigaiarasu et al, 2018). In all the cases of the present study, exit dimensions for the primary and secondary jet are maintained constant.…”
Section: Numerical Studysupporting
confidence: 86%
See 2 more Smart Citations
“…The numerical study was done for the following LTs: 1.0 D p , 1.5 D p , 2.0 D p , 2.5 D p , 3.0 D p , 3.5 D p , 4.0 D p , 4.5 D p , 5.0 D p , 6.0 D p , 7.0 D p , 8.0 D p , 10.0 D p and 15.0 D p . The results for LT 1.0 D p and 1.5 D p obtained from the experimental study correlates well with CFD results (Naren Shankar et al, 2016;Naren Shankar, 2017;Naren Shankar et al, 2018;Thanigaiarasu et al, 2018). In all the cases of the present study, exit dimensions for the primary and secondary jet are maintained constant.…”
Section: Numerical Studysupporting
confidence: 86%
“…At the same time, eddies begin appearing between the gap separating the two jet streams. Wake dominance causes to form a recirculation zone that bends the secondary jet toward primary jet, enhancing mixing (Naren Shankar et al, 2016;Naren Shankar et al, 2018;Thanigaiarasu et al, 2018;Naren Shankar and Dilip Raja, 2019;Naren Shankar, 2019). It is Figure 9 Axial total pressure decay for single jet and CFJ with LT 0.2 D p , 0.5 D p and1.0 D p worth noting that there occurs no IWZ for this LT, which in other way inferred that this LT is not sufficient to produce an influential wake region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above research cited discusses only the total pressure characteristics of the jet in both axial and radial directions. However, Naren Shankar et al (2016), Shankar (2017), Naren Shankar et al (2018), Thanigaiarasu et al (2019), Shankar et al (2020), Naren Shankar et al (2021) and Shankar et al (2021) observed other characteristics of the CFJ such as static pressure variation, velocity variation and streamline behaviour. Before these works, it was assumed that for a subsonic jet, the static pressure will be constant throughout the jet field but in the above mentioned works static pressure varied by 11% above and below atmospheric pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Grooved and chevron nozzles are used as certain techniques in jet flow control (Elangovan and Rathakrishnan 2004;Tide and Srinivasan 2010;Kumar et al 2011). Nozzles are also modified to issue co-flowing jets to control the flow in the subsonic regime (Lovaraju and Rathakrishnan 2011;Shankar et al 2016;Shankar et al 2018;Shankar and Bennett 2019;Thanigaiarasu et al 2019;Shankar and Raja 2020).…”
Section: Introductionmentioning
confidence: 99%